Randomized Double-Blind, Placebo Controlled Safety Study of a Low Molecular Weight Heparinoid in Patients Undergoing Transurethral Resection of the Prostate - ten Cate, Hugo; Henny, Ch Pieter; ten Cate, Jan W; Büller, Harry R; Dabhoiwala, Nosjir F (Thrombosis and Haemostasis, 1987)
In preparation for an efficacy study, the effect of the low molecular weight heparinoid Org 10172 on postoperative blood loss was assessed in a randomized double-blind, placebo controlled study in patients undergoing transurethral resection of the prostate (TURP). Org 10172 and placebo were given twice daily as i.v. injection for three postoperative days starting one hour preoperatively. Three doses of Org 10172 (800, 1600, and 2400 anti-Xa units b.d.) were evaluated against placebo in three consecutive patient blocks respectively. Each block consisted of 20 patients, 15 receiving Org 10172 and 5 patients placebo. The study was discontinued after 9 patients of the third block had completed the protocol because of excessive urinary blood loss. Data analysis showed a dose-dependent increase in postoperative haemoglobin loss, this was not significant for the 800 anti-Xa units b. d. dosage but was significant in those patients treated with 1600 (p <0.05) and 2400 anti-Xa units b.d. (p <0.01).It was concluded that the heparinoid Org 10172 caused a dose dependent increase in urinary blood loss following TURP.
Keywords: Clinical trial; Low molecular weight; Heparinoid; Surgery; Postoperative bleeding